KONSEP RWA BHINEDA PADA KAIN POLENG BUSANA PEMANGKU PENGLURANSAAT UPACARA PENGEREBONGAN DI PURA AGUNG PETILAN, KESIMAN - Pande Putu Wiweka Ari Dewanti; I Gusti Agung Ayu Widyandari Kameswari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
The important point of Rwa Bhineda concept is balance of two unsure which is contrast but can not be separate, example kind and not kind, afternoon-night, hot-cool, and etc. The balance of life is a fundamental concept of life in Bali. Poleng color of pemangku pangluran fashion when pengrebongan ceremony in Pura Agung Petilan Kesiman which is in Rwa Bhineda concept and can be trusted which have magical connotation. The balance of Dharma concept (good) and Adharma (not good). The method which will use in this experiment is descriptive-qualitative method. Purpose in this concept is to connected sanctity of fashion which used by pemangku in pengrebongan ceremony and poleng cloth of the Rwa Bhineda concept. Rwa Bhineda can describe of simple life and not the way should be. Closely relation of Pemangku Pengluran and when pengrebongan ceremony which assume that in every life element of life will be there two of contras power but it is a balance unit which impossible will be the white definition if there is no body to know the black. It will can be taken of individual job of each pemangku pengluran which is connect of the other and can make the whole unit.